Efficacy of low dose of herbicides against weeds in transplanted kharif rice (Oryza sativa L.) (The Journal of Plant Protection Sciences, 2020)
Comparative efficacy of penoxsulum 24 SC against weeds in transplanted kharif rice was studied atRegional Research Sub-Station (New Alluvial Zone), Bidhan Chandra Krishi Viswavidyalaya,Chakdaha, Nadia, West Bengal. The experiment was laid out in a randomized block design with 7treatments and 3 replications. The results revealed that the major weed flora associated with the transplanted rice during kharif season was mainly comprised of Echinochloa colona (30 %), Cyperusdifformis (20 %), Monochoria vaginalis (30 %) and Ludwigia parviflora (20 %). Penoxsulam 24 SCat 0.0225 kg a.i. ha-1 applied at 8-12 days after transplanting was most effective to check all types ofweed population and their growth. This treatment also gave the maximum grain yield (3.53 tha-1) andstraw yield (4.73 tha-1) of rice resulting in lowest weed index (5.61 %). Therefore,
Keywords: Penoxsulum 24 SC; weeds; , transplanted kharif rice